CD56bright NK IL-7Rα expression negatively associates with HCV level, and IL-7-induced NK function is impaired during HCV and HIV infections. Issue 1 (11th April 2017) - Judge, Chelsey J; Kostadinova, Lenche; Sherman, Kenneth E; Butt, Adeel A; Falck-Ytter, Yngve; Funderburg, Nicholas T; Landay, Alan L; Lederman, Michael M; Sieg, Scott F; Sandberg, Johan K; Anthony, Donald D
Abstract : IL-7-dependent NK cell activation and effector function to be impaired in viral infections. Abstract: Several lines of evidence support the concept that NK cells play an important role in control of hepatitis C virus (HCV) infection via cytokine secretion and cytotoxicity. IL-7 is a homeostatic cytokine with a role in T cell development, activation, proliferation, and cytokine secretion. The IL-7Rα chain [cluster of differentiation (CD)127] is expressed on NK cells, with greatest abundance on the CD56 bright CD16 dim/− (CD56 bright ) subset. Here, we measured CD127 expression on CD56 bright, CD56 dim CD16 + (CD56 dim ), or CD56 neg CD16 + (CD56 neg ) NK cell subsets of 25 uninfected donors (UD); 34 chronic HCV-infected, treatment-naiüve; 25 HIV-infected, virally suppressed on antiretroviral therapy (ART); and 42 HCV–HIV-coinfected subjects on ART. Interestingly, CD127 expression on CD56 bright NK cells negatively correlated with HCV plasma levels in HCV monoinfection and HCV–HIV coinfection. IL-7 induced CD69 expression, as well as IFN-γ production, in CD56 bright NK cells and also enhanced the IFN-α-induced CD69 expression on these cells. The latter was impaired in HIV infection. Furthermore, IL-7 induced B cell lymphoma 2 (BCL-2) expression and cell cycling of CD56 bright NK cells, and this effect was impaired in HCV- and HIV-infected subjects. Whereas IL-7-stimulated CD56 bright NK cell degranulation appeared intact in all cohorts, we observed impaired IL-7-activated NK cell cytolytic function in HCV- and HIV-infected subjects. Finally, IL-7-induced phosphorylation of STAT-5 (pSTAT-5) signaling was impaired in NK cells of subjects with chronic viral infection, and this was reversible upon 6 mo of viral suppression with IFN-free HCV therapy. These results implicate that IL-7-dependent NK cell activation and effector function may be other host immune surveillance mechanisms that are impaired in viral infections.